Cervical Spinal Cord Injury Shows Markedly Lower than Predicted Mortality (>72 Hours After Multiple Trauma) From Sepsis and Multiple Organ Failure. (April 2020) - Kamp, Oliver; Jansen, Oliver; Lefering, Rolf; Meindl, Renate; Waydhas, Christian; Schildhauer, Thomas A.; Hamsen, Ume
Background: Sepsis and multiple organ failure (MOF) remain one of the main causes of death after multiple trauma. Trauma- and infection-associated immune reactions play an important role in the pathomechanism of MOF, but the exact pathways remain unknown. Spinal cord injury (SCI) may lead to an altered immune response, and some studies suggest a prognostic advantage for such patients having sepsis or multiple trauma. Yet these findings need to be evaluated in larger cohorts of trauma patients. Methods: Retrospective, multicenter study, using the data of the TraumaRegister DGU. Patients with and without SCI surviving the initial first 72 hours after trauma were matched according to injury pattern and age. Comparative analysis considered morbidity (sepsis, MOF) and hospital mortality. Results: The study population included 800 matched pairs. As intended by the matching process, patients with cervical SCI had an otherwise comparable injury pattern but a higher severity of trauma (mean Injury Severity Score: 36 vs 29, mean number of diagnosis: 5.6 vs 4.4). They had a higher rate of sepsis (15.9% vs 10.9%, P = .005) and MOF (35.9% vs 24.1%, P < .001) while mortality revealed no significant difference (9.5% vs 9.9%, P = .866). Conclusions: Cervical SCI leads to an increased rate of sepsis and MOF but appears to be favorable with respect to outcome of sepsis and MOF following multiple trauma. Further research should focus on the pathomechanisms and the possible arising therapeutic options.